Variation in Articular Cartilage Thickness Among Extant Salamanders and Implications for Limb Function in Stem Tetrapods - Molnar, Julia L. (Frontiers in Ecology and Evolution, 2021)
The size and shape of articular cartilage in the limbs of extant vertebrates is highly variable, yet they are critical for understanding joint and limb function in an evolutionary context. For example, inferences about unpreserved articular cartilage in early tetrapods have implications for how limb length, joint range of motion, and muscle leverage changed over the tetrapod water-land transition. Extant salamanders, which are often used as functional models for early tetrapods, have much thicker articular cartilage than most vertebrate groups, but the exact proportion of cartilage and how it varies across salamander species is unknown. I aimed to quantify this variation in a sample of 13 salamanders representing a broad range of sizes, modes of life, and genera. Using contrast-enhanced micro-CT, cartilage dimensions and bone length were measured non-destructively in the humerus, radius, ulna, femur, tibia, and fibula of each specimen. Cartilage correction factors were calculated as the combined thickness of the proximal and distal cartilages divided by the length of the bony shaft. Articular cartilage added about 30% to the length of the long bones on average. Cartilage was significantly thicker in aquatic salamanders (42±14% in the humerus and 35±8 in the femur) than in terrestrial salamanders (21±7% in both humerus and femur). There was no consistent relationship between relative cartilage thickness and body size or phylogenetic relatedness. In addition to contributing to limb length, cartilage caps increased the width and breadth of the epiphyses by amounts that varied widely across taxa. To predict the effect of salamander-like cartilage correction factors on muscle leverage, a simplified model of the hindlimb of the early tetrapod Acanthostega was built. In this model, the lever arms of muscles that cross the hip at an oblique angle to the femur was increased by up to six centimeters. Future reconstructions of osteological range of motion and muscle leverage in early tetrapods and stem amphibians can be made more rigorous by explicitly considering the possible effects of unpreserved cartilage and justifying assumptions based on available data from extant taxa, including aquatic and terrestrial salamanders.